Constraints on private economy development in China : the case of individual industrial enterprises in Jinning county, Yunnan province - Wen, Ming; Wickramanayake, B.W.E.; Amin, A.T.M. Nurul; Gougeon, P.; Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1992)
The economic China has brought to the reform, the structur e has b een ABSTRACT r eform program initiated in late 1970s in about significant changes in rural areas . Due private econ omy has emerged and the economic diversifi ed. However, the growth of the private economy i s by no mean s a s mooth process . This s tudy a ttempts to analyze the constraints con front ed by the private economy , with focus on the individual indu strial e n terprises in entry, s urvival a nd furt her deve lopment in Jinning county, Yunnan province, China. At the entry s t age , the individual industrial e nterprises encounter probl e ms with submi tting application and r eg istration du e to c umbersome procedures and time taken to obtain the licenses. Capit a l a nd ext ension service are mainly from the entrepreneurs themselves a nd informa l sou rces . Formal sources are far from adequate d u e to the constrain ts of governme n t policy again st individual enterp rises . Negative attitude of the people is also a hindrance. After the enterpri ses have been establis hed, there are a number of con s traints for their survival . F ina n cial man agement and con t rol aff ec t the ir proper operation. Raw materials avai l ability, particularly price fluctuation has a great impact upon these e n terpri ses. Working capital, prejudiced t ax po licy, espec i ally lack of a sound met hod to col l ect tax, a nd unregulated imposition of fees a re a ll obstacl es to the oper a tion of the enterprises . I n addit ion , t h ey a l so h ave to face the problems of selling out l ets, inadequate power supply, low t ec hnology l evel. In t e rms of further deve lopment, the individual industrial e ntrepren eurs a re very sensitiv e to policy changes . They worry abou ttheir stat us and lack of the same development opportunities as co llective a nd state- owned enterprises. Based on the research results, the study proposes a set of recomme ndation s, wh ich is further classifie d into two scenarios by taking into account the Fourteenth Congress of Chinese Communist Party (CCP) held in October, 1992 . Scenario one believes that alt hough CCP has h e ld the congress, policies are still not favorable to the growth of the private economy. Therefore, only a short term plan is made. Scenario two, on the contrary, assumes that after the Fourteenth Congress of CCP, the policies are more favorable to the development of the private economy. Consequently, along term trategic plan is prepared.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology
Keywords: Free enterprise -- China -- Yunnan